Characterization of Fusarium species associated with wilt disease of cucurbits and effectiveness of Trichoderma asperellum as biological enhancer - Aris, Asma (2019)
Fusarium wilt disease caused by Fusarium species is a serious soilborne fungal disease that threatens the production of cucurbits in Malaysia. Despite multiple controls and measures, this economically important pathogenic genus continues intruding the crops. Therefore, this study intends to identify the pathogenicity of Fusarium species from five infected hosts namely cucumber, pumpkin, luffa, gourd and rock melon. Infected cucurbits fruit and leaf obtained from the fields were cultured onto pentachloronitrobenzene agar (PCNB). All isolated fungi were purified using a hyphal tip technique and sub-cultured onto potato dextrose agar (PDA) and carnation leaf agar (CLA) for observing morphological characteristics such as macroconidia, microconidia, formation of chlamydospore, colony features and pigmentation. Ninety-four isolates were successfully recovered from 12 locations throughout Peninsular Malaysia. Isolated fungi were also identified molecularly using translation elongation factor 1-alpha (tef1α) and beta-tubulin (BT) genes sequences analysis. From the findings, the highest number of identified species were F. incarnatum (52 isolates) followed by F. solani (18 isolates), F. proliferatum (17 isolates), F. oxysporum (6 isolates) and F. longipes (1 isolate). A phylogenetic tree was generated from a combination of tef1α and ß-Tub genes sequences. To ascertain the virulence of Fusarium species, all isolates were tested for pathogenicity test by soaking the seeds into 2x106 conidia/mL of conidial suspension for 12 hours. Sterile distilled water served as control. Fusarium solani isolates M1799C and M1800C recorded the highest disease severity of 100% on cucumber, F. solani (C2526P) recorded 93.8% disease severity on pumpkin, F. solani (D2499L) and F. proliferatum (B1777L) recorded 66.75% disease severity on luffa and F. oxysporum (B2547M) recorded 23% disease severity on rock melon. However, no symptoms observed on inoculated gourd plants. In order to eco-friendly control the disease and understand the mechanisms; therefore, Trichoderma asperellum B1902 was testified as a potential plant biological enhancer in wilt-infected cucumber. Efficacy of T. asperellum B1902 was testified by infesting 100 mL/kg inoculum (with concentration 2x106 conidia/mL) onto soil containing infected cucumber plants. After 30 days post-inoculation (dpi), T. asperellum B1902-treated plants increased length of stem, area of total leaves and number of leaves. Furthermore, T. asperellum B1902 also gave rise to the efficiency of photosystem II (PSII) and enhanced the photosynthetic performance of cucumber plants. The information channeled from this study leads a foundational knowledge for better management in controlling Fusarium wilt infection.